Physical activity level, sociodemographic and family aspects, healthy habits and health care for older adults: Comparison the level of physical activity in older adults - Hernández-Carrillo, Mauricio; Quiroz-Mora, Carlos Andrés; Betancourt-Pena, Jhonatan (Universidad y Salud, 2021)
Introduction: The practice of physical activity in the elderly is affected by social, cultural and demographic aspects. Objective: To compare the relationship between physical activity level and various population and medical characteristics (sociodemographic, family, healthy habits, illnesses, and health care) in a group of older adults. Materials and methods: An observational cross-sectional study was conducted with an elderly population from Cali (Colombia), using a simple standardized sampling. The International Physical Activity Questionnaire (IPAQ) was used to assess physical activity, comparing groups with intense-moderate physical activity (IMPA) and those showing low-inactive physical activity (LIPA). Results: The study included 189 and 364 patients with IMPA and LIPA, respectively. Statistically significant differences were found for the variables: housing area, employment, source of income and dependency (p=0.000); family composition (p=0.008), living alone (p=0.031), social network (p=0.000), alcohol consumption, exercise, high blood pressure, medication use (p=0.000), diabetes mellitus (p=0.045), body mass index (p=0.032), health insurance affiliation, distance from health care center, and costs (p=0.000). Conclusions: Habits such as alcohol and tobacco consumption together with diseases such as high blood pressure and diabetes mellitus are related to LIPA. Also, older adults residing in rural areas showed higher activity levels.